2017
DOI: 10.1590/s1518-8787.2017051006549
|View full text |Cite
|
Sign up to set email alerts
|

Institutional violence and quality of service in obstetrics are associated with postpartum depression

Abstract: OBJECTIVE To investigate the association between institutional violence in obstetrics and postpartum depression (PP depression) and the potential effect of race, age, and educational level in this outcome.METHODS This is a cross-sectional study about the health care conditions for the maternal and child population of the Federal District, Brazil, carried out in 2011. The study has used a probabilistic sample of 432 women, whose children were aged up to three months, stratified by clusters. Indicators of instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 16 publications
3
28
1
20
Order By: Relevance
“…Consequences of disrespect and abuse during childbirth on women's mental health outcomes have been mainly focused on the risk of post-traumatic stress disorder (Reed et al., 2017). To our knowledge only one previous study evaluated the influence of disrespect and abuse experiences during childbirth on postpartum depression occurrence (Souza et al., 2017). Findings of this study are consistent to ours as the authors found a positive cross-sectional association between institutional violence in obstetric care and postpartum depression, with physical violence between the parturient and health care providers as the most important determinant.…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of disrespect and abuse during childbirth on women's mental health outcomes have been mainly focused on the risk of post-traumatic stress disorder (Reed et al., 2017). To our knowledge only one previous study evaluated the influence of disrespect and abuse experiences during childbirth on postpartum depression occurrence (Souza et al., 2017). Findings of this study are consistent to ours as the authors found a positive cross-sectional association between institutional violence in obstetric care and postpartum depression, with physical violence between the parturient and health care providers as the most important determinant.…”
Section: Discussionmentioning
confidence: 99%
“…In India, given the hierarchical nature of the society, it is imperative to study the access to health facilities and women’s experience of receiving healthcare with dignity within a socioeconomic framework. Studies based on experiences of Latin American women of indigenous origin insist that women from poor, indigenous or socially backward classes receive ‘triple discrimination’ that is, by being female, being an ethnic minority and of lower socioeconomic status 19. Even in egalitarian European societies, women facing economic hardships and negative life events with the least social support have higher chance of experiencing LRV than their counterparts 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Procedures not technically indicated can lead to consequences and iatrogenies, with avoidable effects on the health of the woman and the baby, such as dystocia at childbirth, hemorrhages and neonatal hypoxia, as well as female dissatisfaction and postpartum depression [5][6][7] .Obstetric violence is a gender-based violence, targeting specifically women and permeating unequal power relations in our society [8][9] . In countries such as Venezuela and Argentina, for example, OV was typified in national legislation as violence against women 4 .…”
Section: Introductionmentioning
confidence: 99%